2018
DOI: 10.7554/elife.38889
|View full text |Cite
|
Sign up to set email alerts
|

The flow responsive transcription factor Klf2 is required for myocardial wall integrity by modulating Fgf signaling

Abstract: Complex interplay between cardiac tissues is crucial for their integrity. The flow responsive transcription factor KLF2, which is expressed in the endocardium, is vital for cardiovascular development but its exact role remains to be defined. To this end, we mutated both klf2 paralogues in zebrafish, and while single mutants exhibit no obvious phenotype, double mutants display a novel phenotype of cardiomyocyte extrusion towards the abluminal side. This extrusion requires cardiac contractility and correlates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 123 publications
(181 reference statements)
7
65
4
1
Order By: Relevance
“…Considering that genetic compensation can significantly alter gene expression in ZF mutants [37], we assessed potential crossregulation between egr1, klf2a, and klf2b. Contrary to Rasouli et al [29] we did not detect significative compensatory expression of klf factors in our klf2 mutants, suggesting that our alleles do not activate genetic compensation [38]. Rather, we found that egr1 was significantly downregulated in klf2b mutants (S3A and Supplementary Table 1), potentially explaining some of the shared common targets.…”
Section: Egr1 Klf2a and Klf2b Control Unique Valve-related Transcricontrasting
confidence: 99%
See 1 more Smart Citation
“…Considering that genetic compensation can significantly alter gene expression in ZF mutants [37], we assessed potential crossregulation between egr1, klf2a, and klf2b. Contrary to Rasouli et al [29] we did not detect significative compensatory expression of klf factors in our klf2 mutants, suggesting that our alleles do not activate genetic compensation [38]. Rather, we found that egr1 was significantly downregulated in klf2b mutants (S3A and Supplementary Table 1), potentially explaining some of the shared common targets.…”
Section: Egr1 Klf2a and Klf2b Control Unique Valve-related Transcricontrasting
confidence: 99%
“…However, klf2 expression and function are not restricted to the AVC [24,25]. Indeed, klf2 also plays a role in ventricular trabeculation [29] and in controlling the shape of endothelial cells located in the ventricle [22], suggesting that other flow-inducible transcription factors are required in the AV canal to modulate specific AVC cell responses to flow. A possible candidate could be the only paralog of klf2a in zebrafish, klf2b, of unknown function in valve morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…We did, however, observe collapsed endocardial morphology and a significant reduction in OFT endocardial cell number in one out of eleven klf2 mutant embryos ( Fig. S7-1C), suggesting the possibility of a poorly penetrant phenotype; similarly, defects in atrioventricular canal morphogenesis also appeared with ~10% penetrance in klf2 mutants by 48 hpf (Rasouli et al, 2018). Thus, although we cannot rule out some contribution of Klf2 factors to OFT endocardial expansion, it seems that they are not essential.…”
Section: Klf2a and Klf2b Are Not Essential For Endocardial Expansion mentioning
confidence: 80%
“…To examine the roles of klf2a and its paralog klf2b in OFT assembly, we examined OFT endocardial cell number in embryos homozygous for mutations in both klf2a and klf2b (henceforth called klf2 mutants) (Rasouli et al, 2018) at 51 hpf. OFT endocardial cell number in ten out of eleven klf2 mutants appeared remarkably similar to their control siblings ( Fig.S7-1A,B,D), suggesting that Klf2 factors do not govern OFT endocardial expansion.…”
Section: Klf2a and Klf2b Are Not Essential For Endocardial Expansion mentioning
confidence: 99%
See 1 more Smart Citation